(3GdhGaj HGdhajGJ GdCYjGf Gdeced dZQHGd GdReGfs - (3YHO Gddg Hf Ydj Hf eMeO GdUaOj GdTajQjs ((3eMeO Hf Ydi GdThcGfi s)
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdOjGf , ebdH GdCReGf , cd jhe gh ai TCf Ke YbHg hajGJ SfI (B750 (3g` s
(3BNQgG (B:s
(3BNQg ef hajGJ SfI (B1068 (3g` bhdg (B: (3hajgG Jhai GdbGVi MGce eOjfI CHj YQjT hGHf bVGFgG Gdabjg GdbGVi SQGL GdOjf YeQ Hf CMeO CHh GdaVGFd GdCSOi s
(3cJHJ GdYfhGfGJ HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda SfI (B1218s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdbGVi CMeO Hf eMeO RHGQI GdNGUI HUfYGA (B((3JQGLe (B77) s
Keywords: (3GdJGQjNs